Wearing failure as a badge of innovation - Ferreira, J.; Fernandes, C.; Ferreira, F. (Proceedings of the 2020 ACIEK International Conference, 2020)
Innovation is a widely acknowledged key component of corporate performance management. However, most of the literature on this topic has tended to focus on determinants of corporate failure, thereby neglecting to look at the role of innovation failure in triggering innovative initiatives. By using a sample of companies covered by 2014 Community Innovation Survey data and applying econometric models, this study sought to analyze the impacts of innovative project failure. The results show that innovation failure is negatively correlated with companies’ experience and acquisition of external knowledge. The main findings are consistent with the scarce literature on this research topic, and they highlight the positive role that companies’ accumulated experience has in their assimilation of knowledge flows.